Finding Tools for Microform Publishing Projects. A Preliminary Union List. METRO Miscellaneous Publication No. 13 - New York Metropolitan Reference and Research Library Agency, NY.; Myrick, William J., Jr.; New York Metropolitan Reference and Research Library Agency, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This union list identifies 75 microform publications for which the staff of 24 U.S. and Canadian research libraries have produced indexes, analytic cards, or other content guides. Each entry includes the name of the publisher, the format and types of entries in the finding tool, entry verification authority, and the name of the reporting library. The list has many cross-references and, for 13 of the titles, more than one index is identified. Reporting libraries are listed. (Author/RAA)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Cataloging; Microforms; Research Libraries; Union Catalogs; Reference Materials, Bibliographies